Effects of lower body cold water immersion on performance submaximal isometric contractions - Willems, M. E. T.; Clarkson, S. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction Muscle temperature influences the performance of successive isometric contractions of m. quadriceps femoris (QF) (Edwards et al., 1972). Muscle fatigue during sustained isometric contractions results in increased force fluctuations, i.e. a decline in steadiness. Such fatigue is associated with compensatory neuromuscular responses but less is known on the effect of cold water immersion on submaximal isometric performance. We examined the effect of cold water immersion of the lower body on the performance of submaximal isometric contractions of m.quadriceps femoris. Methods: Men (n=11, 26±4 yr, 179±9 cm, 79±14 kg, thigh skin fold: 15 ± 1 mm) were tested in a temperature-controlled laboratory (control (C), 19°C) and following cold water immersion (CWI, 12°C) of the lower body for 30minutes and ice-pack cooling of the leg during muscle testing. Skin temperature during muscle testing in CWI conditions was 12±1°C (Edale Instruments, UK). Subjects produced maximal voluntary isometric force (MVIF) of QF (knee angle 90°), a 20%MVIF until exhaustion and 2 seconds after completion of the 20%MVIF a measurement of MVIF to quantify fatigue. Steadiness during 20%MVIF was quantified by the coefficient of variation (SD/mean·100%). Surface EMG (Bagnoli-8, Delsys, USA) of m.vastus medialis (VM), m.rectus femoris (RF) and m.vastus lateralis (VL) was analysed for root mean square (RMS) and median frequency (MF). Data were analysed with 2-way ANOVA and paired t-tests with significance set at P<0.05. Results: There were no differences between conditions for MVIF (C: 616±112 N, CWI: 615±102 N), steadiness at similar time periods during 20%MVIF (e.g. 90-100% of time to fatigue (TtF), C: 9.2±3.5%; CWI: 7.4±2.3%) and fatigue index (C: 30±16%, CWI: 29±11%). CWI resulted in 34% higher TtF (C: 319±121s, CWI: 426±166 s) (P<0.01). During 20%MVIF, changes in RMS were lower for VL after CWI (0-10% to 90-100%TtF, C: 25±5 to 48±14%RMS; CWI: 21±4 to 34±8%RMS) with substantially lower MF values for all muscles after CWI and decreased MF values for VL only for control (0-10% to 90-100%TtF, C: 96±15 to 87±18 Hz; CWI: 76±9 to 74±14 Hz) (all P<0.01). Discussion: Cold water immersion increased the time to fatigue for a sustained 20% isometric force of m.quadriceps femoris. Neuromuscular responses to cold water immersion were different for submaximal isometric contractions of the m.quadriceps femoris with lower levels of activation and no decrements in median frequency for the m.vastus lateralis but without an overall effect on steadiness for the m. quadriceps femoris. Peripheral mechanisms contributing to isometric fatigue of submaximal sustained contractions following cold water immersion seem to be muscle-dependent.